2021
DOI: 10.1097/ajp.0000000000000944
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Magnesium Sulfate and Peripheral Nerve Blocks

Abstract: Objectives: With the popularization of ultrasound, nerve blocks have been widely implemented in current clinical practice. Although, they have seen limited success due to their shorter duration and suboptimal analgesia. Magnesium sulfate as a local anesthetic adjuvant for peripheral nerve blocks could enhance the effects of local anesthetics. However, previous investigations have not thoroughly investigated the analgesic efficacy of magnesium sulfate as an adjunct to local anesthetics for peripheral nerve bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
(147 reference statements)
1
5
0
Order By: Relevance
“…Similar to our findings, Zeng et al discovered that adjuvant MgSO4 significantly decreased the total amount of analgesics consumed on the first postoperative day relative to the control group; 23 a subgroup analysis showed that MgSO4 significantly decreased the total quantity of analgesics consumed in TAP blockade patients. 21 Additionally, earlier research found that a single 50 mg bolus dose of MgSO4 given to children for caudal analgesia was effective in preventing intraoperative distress and delaying the beginning of postoperative pain.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, Zeng et al discovered that adjuvant MgSO4 significantly decreased the total amount of analgesics consumed on the first postoperative day relative to the control group; 23 a subgroup analysis showed that MgSO4 significantly decreased the total quantity of analgesics consumed in TAP blockade patients. 21 Additionally, earlier research found that a single 50 mg bolus dose of MgSO4 given to children for caudal analgesia was effective in preventing intraoperative distress and delaying the beginning of postoperative pain.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent meta-analysis of randomized controlled trials that evaluated 22 trials involving 1453 patients, Zeng and colleagues concluded that the addition of magnesium as an adjuvant to peripheral nerve blocks prolonged the total duration of sensory blockade, reduced VAS scores at 6 and 12 hours postsurgery, and reduced analgesic use in the first 24 hours postsurgery. The authors also reported a 44% reduction in the incidence of nausea and vomiting in patients receiving magnesium as an adjuvant to local anesthetic compared with patients receiving local anesthetic alone (95% confidence interval: 0.35-0.92, I 2 =0%; P =0.02) 27…”
Section: Discussionmentioning
confidence: 94%
“…The authors also reported a 44% reduction in the incidence of nausea and vomiting in patients receiving magnesium as an adjuvant to local anesthetic compared with patients receiving local anesthetic alone (95% confidence interval: 0.35-0.92, I 2 = 0%; P = 0.02). 27 Despite significant evidence supporting the use of magnesium in peripheral nerve blocks, not all reports support using magnesium as an adjunct. Zoratto et al, 28 in a prospective randomized control trial studying the addition of magnesium to ropivacaine in ACBs for TKA, reported no analgesic benefit when compared with the control group that only received a ropivacaine ACB.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of magnesium and buprenorphine, individually as adjuvants to local anesthetic during regional anesthesia, has been shown to increase the duration of regional blocks, decrease pain scores, decrease opioid consumption, and decrease side effects from increased opioid consumption [28][29][30]. However, there are very few studies examining the addition of adjuvant medications to local anesthetic in regional anesthesia specifically for cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%